Criminal governance and state capacity in Mexico: Citizen support for political-criminal pacts - Hernández Morales, Alan Salvador (2025)
Introduction: The complexity that criminal governance has acquired through predatory and clientelistic actions by criminal groups has called into question the state's capacity to protect the population. In Mexico, as in other countries in the region, this has placed in the public debate the relevance of pacts between the government and criminals as a measure to reduce violence. Objective: Therefore, this research aims to understand the factors that influence people's support for a political-criminal arrangement, as well as those that contribute to considering criminal organizations legitimate and approving the impunity of their members. Methodology: To this purpose, we conducted an econometric analysis based on two nationally representative surveys. Conclusions: The results suggest that when clientelistic criminal governance is exercised and when there is less state capacity in the area of security, citizen approval of the pacts between the government and criminal groups increases, as well as their legitimacy. On the contrary, when criminal governance is violent, the population's repudiation of criminals increases and there is greater pressure on the government to fight them.